Matrix Metalloproteinase Responsive, Proximity‐Activated Polymeric Nanoparticles for siRNA Delivery. (6th February 2013) - Li, Hongmei; Yu, Shann S.; Miteva, Martina; Nelson, Christopher E.; Werfel, Thomas; Giorgio, Todd D.; Duvall, Craig L.
Abstract Small interfering RNA (siRNA) has significant potential to evolve into a new class of pharmaceutical inhibitors, but technologies that enable robust, tissue‐specific intracellular delivery must be developed before effective clinical translation can be achieved. A pH‐responsive, smart polymeric nanoparticle (SPN) with matrix metalloproteinase (MMP)‐7‐dependent proximity‐activated targeting (PAT) is described here. The PAT‐SPN is designed to trigger cellular uptake and cytosolic delivery of siRNA once activated by MMP‐7, an enzyme whose overexpression is a hallmark of cancer initiation and progression. The PAT‐SPN is composed of a corona‐forming polyethylene glycol (PEG) block, an MMP‐7‐cleavable peptide, a cationic siRNA‐condensing block, and a pH‐responsive, endosomolytic terpolymer block that drives self‐assembly and forms the PAT‐SPN core. With this novel design, the PEG corona shields cellular interactions until it is cleaved in MMP‐7‐rich environments, shifting the SPN ζ‐potential from +5.8 to +14.4 mV and triggering a 2.5 fold increase in carrier internalization. The PAT‐SPN exhibits pH‐dependent membrane disruptive behavior that enables siRNA escape from endo‐lysosomal pathways. Intracellular siRNA delivery and knockdown of the model enzyme luciferase in R221A‐Luc mammary tumor cells is significantly increased by MMP‐7 pre‐activation (p < 0.05). These combined data indicate that the PAT‐SPN provides a promising new platform for tissue‐specific, proximity‐activated siRNA delivery to MMP‐rich pathological environments.